2012
DOI: 10.1371/journal.pone.0033249
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Memory Impairment Is Associated with Disrupted Multivariate Epigenetic Coordination in the Hippocampus

Abstract: Mounting evidence linking epigenetic regulation to memory-related synaptic plasticity raises the possibility that altered chromatin modification dynamics might contribute to age-dependent cognitive decline. Here we show that the coordinated orchestration of both baseline and experience-dependent epigenetic regulation seen in the young adult hippocampus is lost in association with cognitive aging. Using a well-characterized rat model that reliably distinguishes aged individuals with significant memory impairmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 46 publications
7
81
1
Order By: Relevance
“…Age-related deficits revealed by this model are associated with disrupted epigenetic regulation in the hippocampus (Castellano et al, 2012), and are sensitive to rescue by pharmacological intervention targeting a variety of mechanisms (Koh et al, 2013;. A pilot study in a small number of aged rats revealed that, consistent with results for exploratory activity in young subjects (Fig.…”
Section: Pretraining Evx Administration Fails To Ameliorate Hippocampsupporting
confidence: 65%
See 1 more Smart Citation
“…Age-related deficits revealed by this model are associated with disrupted epigenetic regulation in the hippocampus (Castellano et al, 2012), and are sensitive to rescue by pharmacological intervention targeting a variety of mechanisms (Koh et al, 2013;. A pilot study in a small number of aged rats revealed that, consistent with results for exploratory activity in young subjects (Fig.…”
Section: Pretraining Evx Administration Fails To Ameliorate Hippocampsupporting
confidence: 65%
“…Redundant Place-Cue Training-Approximately two weeks after standard background training, rats were tested on a redundant place-cue task (RPC) in a new spatial environment (Castellano et al, 2012). Training consisted of 15 trials with an escape platform held in a constant location (15 sec intertrial interval), and a probe trial 24 hr after the first training trial.…”
Section: Water Maze Assessmentsmentioning
confidence: 99%
“…In fact, exposure to a novel environment produced increased levels of ERK1/2 dependent H3 phosphorylation and acetylation that was abolished by environmental habituation (Sarantis et al 2012). Similarly, context exposure alone produced increased H3K9me2 in the CA1 (Gupta-Agarwal et al 2012) and exposure to a visible-platform control condition produced similar changes in H3 acetylation to those seen after MWM training (Castellano et al 2012). With respect to DNA methylation, the specificity of the changes observed in response to the context and shock pairing is dependent on the gene of interest, with some genes, including egr1/zif268 and bdnf exon 1, exhibiting similar modifications when shock and context are presented individually as when they are presented in combination (Lubin et al 2008;Miller et al 2010).…”
Section: Euchromatin-associated Modifications Enhance Memorymentioning
confidence: 84%
“…Using peptide array technology, Castellano et al (2012) showed that several of their purchased antibodies recognized various histone modifications in addition to the ones supposedly targeted by their antibodies. This lack of antibody specificity has important implications for both past and future studies that examine how combinatorial patterns of histone modifications work together to regulate gene expression.…”
Section: General Considerations and Limitationsmentioning
confidence: 99%
“…Furthermore, mice with deletion of the Hdac2 gene showed enhanced LTM, in response to fear conditioning, while overexpression of Hdac2 in the mouse brain decreased LTM (47). Several other studies have also indicated that limiting HDAC2 levels is critical for optimal cognitive ability during aging (54)(55)(56). HDAC2 was found to be elevated in Alzheimer's disease brains and in mouse models for neurodegenerative disease, which have defects in spatial memory and fear conditioning (54).…”
Section: Histone Acetylationmentioning
confidence: 98%